Characterization of PM10-Bound Polycyclic Aromatic Hydrocarbons and Associated Carcinogenic Risk in Bangkok, Thailand - Amornphat Tadsanaprasittipol (Applied Sciences, 2021)
Concentrations of ambient particulate-bound polycyclic aromatic hydrocarbons (pPAHs) were measured in PM10 samples collected at roadside, industrial and urban background sites in Bangkok between May 2013 and May 2014. The annual average PM10 concentrations were not significantly different between the roadside (56.4 ± 27.3 µg m−3) and industrial (51.0 ± 31.1 µg m−3) sites. The lowest annual mean PM10 was observed at the urban background site (39.8 ± 22.2 µg m−3). Seasonal variations of pPAHs were observed at the three sampling sites. The total pPAHs ranged between 1.09 and 13.10 ng m−3 (mean 4.85 ± 2.51 ng m−3), 1.49 and 9.39 ng m−3 (mean 3.84 ± 2.01 ng m−3) and 0.77 and 5.20 ng m−3 (mean 2.28 ± 1.16 ng m−3) at the roadside, industrial and urban background sites, respectively. The observed annual average benzo[a]pyrene concentrations were 0.47 ± 0.39 ng m−3, 0.35 ± 0.27 ng m−3 and 0.24 ± 0.19 ng m−3 at the roadside, industrial and urban background sites. Long-term carcinogenic health risk of inhalation exposure expressed as the toxicity equivalent to benzo[a]pyrene concentrations were calculated as 0.83, 0.72 and 0.39 ng m−3 at the industrial, roadside and urban background sites, respectively. The composition of pPAHs plays an important role in the carcinogenicity of a PAHs mixture.